Kepatuhan Wajib Pajak Kendaraan Bermotor: Analisis Pengaruh Kualitas Sistem Layanan Pajak dan Literasi Perpajakan : (Studi di SAMSAT Kabupaten Dompu) - Nayasafitri Ramadani; Nurul Hayat; Dian Urna Fasihat (AKUNTANSI 45, 2026)
This study aims to examine the effect of tax service quality and tax literacy on motor vehicle taxpayer compliance at SAMSAT Dompu Regency. This research uses a quantitative approach with a survey method. The population in this study is all registered motor vehicle taxpayers at SAMSAT Dompu Regency totaling 21,074 taxpayers, with a sample of 100 respondents determined using the Slovin formula with accidental sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics 32.0. The results show that: (1) tax service quality has a positive and significant effect on motor vehicle taxpayer compliance (t = 3.634, Sig. <0.001); (2) tax literacy has a positive and significant effect on motor vehicle taxpayer compliance (t = 4.015, Sig. <0.001); and (3) tax service quality and tax literacy simultaneously have a positive and significant effect on motor vehicle taxpayer compliance (F = 31.659, Sig. <0.001) with a coefficient of determination (R²) of 0.395 or 39.5%. These findings indicate that improving the quality of tax services and increasing community tax literacy are two strategic factors in increasing motor vehicle taxpayer compliance in Dompu Regency.